Organizational Change in Elementary School. Does Teacher Commitment Important? - Windasari Windasari; Erny Roesminingsih; Syunu Trihantoyo (Jurnal Paedagogy, 2022)
This study aims to analyze theacher commitment’s effect on organizational change in elementary school. This study used a quantitative approach using simple linear regression test data analysis techniques. The populations of this study were teachers and principals of elementary schools in East Java with a total population of 55,152. The research sample was 396 respondents with simple random sampling method. The research questionnaire was prepared using a Likert scale of 1-5 and distributed via Google form. The results of this study indicated that teacher commitment influences organizational change in elementary schools. Moreover, affective commitment, normative commitment and continuing commitment impacted organizational changes in elementary schools.